2016
DOI: 10.1016/j.jbtep.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Disgust- and anxiety-based emotional reasoning in non-clinical fear of vomiting

Abstract: These findings are consistent with the view that disgust-based ER is involved in fear of vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 36 publications
0
22
0
3
Order By: Relevance
“…sensitivity (Verwoerd et al, 2016). Furthermore, disgust and anxiety based emotional reasoning was found to significantly predict high and low fear of vomiting, suggesting that disgust and emotional reasoning may play a role in the development of SPOV (Verwoerd et al, 2016).…”
Section: Aetiologymentioning
confidence: 90%
See 2 more Smart Citations
“…sensitivity (Verwoerd et al, 2016). Furthermore, disgust and anxiety based emotional reasoning was found to significantly predict high and low fear of vomiting, suggesting that disgust and emotional reasoning may play a role in the development of SPOV (Verwoerd et al, 2016).…”
Section: Aetiologymentioning
confidence: 90%
“…Ten studies explored the phenomenology of SPOV and found that increased nausea, intrusive imagery of vomiting, disgust and locus of control were significant features of SPOV (Davidson, Boyle, & Lauchlan, 2008;Holler et al, 2013;Lelliott et al, 1991;Lipsitz et al, 2001;Price, Veale, & Brewin, 2012;van Hout & Bouman, 2012;van Overveld, de Jong, Peters, van Hout, & Bouman, 2008;Veale & Lambrou, 2006;Verwoerd, van (Price et al, 2012).…”
Section: Diagnosis and Phenomenology Of Spovmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, animals like spiders and snakes may be associated with disgust due to their physical features, including being creepy, hairy, or slimy [4]. Research has shown that disgust proneness is associated with a fear of vomiting [60,61], and it remains significantly associated with spider fear [62,63] and BII fear [64] even after controlling for trait anxiety. Disgust also appears to affect cognitions surrounding a fear of vomiting.…”
Section: Disgust and Specific Phobiasmentioning
confidence: 99%
“…Disgust also appears to affect cognitions surrounding a fear of vomiting. Compared to individuals with low fear of vomiting, highly vomit-fearful individuals used disgust information presented after an ambiguous scenario to predict that a character in a scenario had a higher chance of becoming ill, a form of reasoning known as disgust-based emotional reasoning [61]. Emotional reasoning often leads to overestimation of threat, even in objectively safe situations, and is hypothesized to contribute to the maintenance of dysfunctional beliefs [65].…”
Section: Disgust and Specific Phobiasmentioning
confidence: 99%